Lack of Association between the 4234G/C X-Ray Repair Cross- Complementing 2 ( XRCC2 ) Gene Polymorphism and the Risk of Endometrial Cancer among Polish Population - Hanna Romanowicz; Magdalena Bryś; Ewa Forma; Beata Smolarz (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Objective: One of the major causes of carcinogenesis is loss of genome stability. The double strand break DNA repair pathway, including X-ray repair cross complementing group 2 (XRCC2) gene, is implicated in maintenance integrity of genome and therefore could affect endometrial cancer (EC) risk. The purpose of this study was to evaluate the clinical significance of the XRCC2 4234G/C (rs3218384) gene single nucleotide polymorphism (SNP) in endometrial cancer patients.  Material and Methods: The study included 1632 patients: 808 with endometrial cancer and 824 healthy controls. XRCC2 4234G/C (rs3218384) polymorphism was genotyped by the PCR-RFLP (restriction fragment-length polymorphism) method. The associations of the analysed genotypes and clinical data at diagnosis have been evaluated.  Results: The frequencies of genotype of the 4234G/C XRCC2 polymorphism did not differ significantly between patients and controls. The current study failed to show the correlation between XRCC2 genotypes and histological grading. Analyzed polymorphism was also unrelated to the patient age, body mass index, number of pregnancies, uterine bleeding, endometrial ultrasound transvaginal, diabetes and hypertension.  Conclusion: This is the first article of 4234G/C polymorphism in XRCC2 gene and EC risk. The current study failed to show the association between the 4234G/C XRCC2 polymorphism and clinical data of patients with endometrial cancer.